2003
DOI: 10.1523/jneurosci.23-24-08489.2003
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Tonically Active Neurons in the Monkey Striatum Discriminate between Motivationally Opposing Stimuli

Abstract: The striatum is involved in the control of appetitively motivated behavior. We found previously that tonically active neurons (TANs) in the monkey striatum show discriminative responses to different stimuli that are appetitive or aversive. However, these differential responses may reflect the sensory qualities of the stimulus rather than its motivational value. In the present study, we sought to define more precisely the relationship between the particular aspect of the response of TANs and the motivational va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
113
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 41 publications
8
113
0
Order By: Relevance
“…This is consistent with numerous reports that tonically active interneurons (TANs) in the striatum, which are believed to be cholinergic, develop a characteristic pause-rebound firing pattern in response to reward-predictive stimuli (Apicella et al, 2011;Matsumoto et al, 2001;Ravel et al, 2003). Interestingly, task-related modulation of TAN firing appears to be more prominent during simple Pavlovian (stimulus-reward) conditioning than during cue-triggered instrumental (stimulus-response-reward) conditioning (Apicella et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with numerous reports that tonically active interneurons (TANs) in the striatum, which are believed to be cholinergic, develop a characteristic pause-rebound firing pattern in response to reward-predictive stimuli (Apicella et al, 2011;Matsumoto et al, 2001;Ravel et al, 2003). Interestingly, task-related modulation of TAN firing appears to be more prominent during simple Pavlovian (stimulus-reward) conditioning than during cue-triggered instrumental (stimulus-response-reward) conditioning (Apicella et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…The striatum can be subdivided into a dorsal (primarily caudate and putamen) and a ventral (primarily nucleus accumbens) components. Although more reward-related neurons are found in the ventral striatum (Apicella et al, 1991), research also suggests that some neurons in the dorsal striatum, specifically the caudate, also respond to reward (Kawagoe et al, 1998(Kawagoe et al, , 2004Lauwereyns et al, 2002;Ravel et al, 2003;Takikawa et al, 2002;Watanabe et al, 2003). This is supported by neuroimaging studies implicating the dorsal striatum in processing an array of rewards and punishments, such as money Delgado et al, 2000Delgado et al, , 2003Delgado et al, , 2004Elliott et al, 2000Elliott et al, , 2004Knutson et al, 2001aKnutson et al, , 2001b, liquids and odors (Berns et al, 2001;Gottfried et al, 2002;O'Doherty et al, 2002O'Doherty et al, , 2003O'Doherty et al, , 2004.…”
Section: Discussionmentioning
confidence: 96%
“…This could also be the reason that, in previous studies, TANs responded selectively to reward-associated stimuli such as the click noise of a solenoid valve to deliver liquid reward, or selectively to reward itself when immediately followed by conditioned orofacial movement (Kimura et al, 1984;Apicella et al, 1991;Aosaki et al, 1994bAosaki et al, , 1995Ravel et al, 1999). Ravel et al (2003) recently reported that TANs discriminate between reward and no-reward (airpuff and loud sound) stimuli in terms of the temporal pattern of responses. The present study did not show a differential temporal pattern in the responses to outcome-associated instructions but did show a difference in the temporal response patterns between the instruction responses and GO responses (Figs.…”
Section: Is Reward Special For Activity Of Tans?mentioning
confidence: 99%
“…Tonically active neurons (TANs), presumed cholinergic interneurons in the striatum (Wilson et al, 1990;Aosaki et al, 1995;Kawaguchi et al, 1995), were initially characterized by the responses to reward-associated stimuli (Kimura et al, 1984;Apicella et al, 1991;Kimura, 1992;Raz et al, 1996), by the evolution of responses via behavioral learning (Aosaki et al, 1994b), and by the involvement of the nigrostriatal dopaminergic system in the responses (Aosaki et al, 1994a). It was subsequently shown that TANs respond not only to reward-associated stimuli but also to aversive stimuli such as an airpuff on the face (Ravel et al, 1999;Blazquez et al, 2002;Ravel et al, 2003). Furthermore, the responses of TANs in the caudate nucleus to visual cues for eye movement tasks were selective to the contralateral visual field but much less selective to whether the cue was associated with reward or no-reward outcome (Shimo and Hikosaka, 2001).…”
Section: Introductionmentioning
confidence: 99%